Pengaruh Bauran Promosi, Sales Cycle, Keunggulan Bersaing, Relationship Merketing, Cross Selling, Terhadap Kinerja Pemasaran Produk Asuransi Jiwa Pada PT.Asuransi Jiwa Brilife Kantor Wilayah Manado - Rundengan, Marsela gledis (Universitas Sam Ratulangi, 2019)
Marketing performance is a measure of achievement obtained from the process of overall marketing activities of an organization or company. This study aims to determine the effect of Promotion Mix, Sales Cycle, Competitive Advantage, Relationship Marketing, and Cross Selling to Marketing Performance of life insurance products in the Brilife regional office Manado. The method used is the analysis of Multiple Linear Regression. The sample used was 110 active customers who lived in the city of Manado. The results showed that the Promotion Mix had a positive and significant effect on Marketing Performance, Sales Cycle had a positive and significant effect on Marketing Performance, competitive advantage had a positive and significant effect on Marketing Performance, Relationship Marketing had a positive and insignificant effect on Marketing Performance, Cross Selling negatively affected Performance Marketing.Keywords: Promotion Mix, Sales Cycle, Competitive Advantage, Relationship Marketing, cross selling, marketing performance